Fenomena Unmet Need di Kampung KB - Saidi Santoso; Yoyok Hendarso; Elisa Wildayana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to analyze the phenomenon of Unmet need in KB village. This research method is a quantitative analysis using secondary data from the 2021 Family Data Collection (PK 21). The population used was all PUS in the Rambang Kapak Tengah District with a sample of 326 PUS. Descriptive statistical analysis used in this study through three stages, namely: univariate analysis, bivariate analysis (Chi Square) and multivariate. The results of this study are three factors that can influence Unmet need, including age at first marriage, number of children and age of wife. The conclusion of the research is that after being analyzed there are three factors that influence unmet need and there are three factors that do not affect Unmet need in the KB village. Keywords: Don't want Children, Unmet Need, Want Delayed Children